Zika, sexual transmission and prudent public health policy. (July 2017) - Folkers, K.M.; Caplan, A.L.; Igel, L.H.
Highlights: There is significant debate about whether the Zika virus can be considered a sexually transmitted infection (STI). Epidemiologically, Zika may not be an STI, but considering it one contributes to prudent public health policy. Classifying Zika as an STI may increase access to testing, identify at risk partners, and educate the public on safer sex.